مدي توافر المقومات الأساسية لتطبيق الموازنة الصفرية على الجامعات الليبية (دراسة حالة جامعة الزاوية) - الزروق, مروة محمد (جامعة الوادي - University of Eloued, 2020)
ملخص الدراسة: هدفت الدراسة إلي التعرف علي مدي توافر المقومات الأساسية لتطبيق الموازنة الصفرية في الجامعة الليبية (دراسة حالة لجامعة الزاوية)، تكون مجتمع الدراسة وعينتها من جامعة الزاوية، ولتحقيق أهداف الدراسة تم استخدام المنهج الوصفي التحليلي، وتكونت عينة الدراسة (45) من موظفي القسم المالي جامعة الزاوية، واستخدمت الدراسة استبانه ، واستخدمت الباحثة العديد من الأساليب الإحصائية الوصفية مثل (المتوسطات الحسابية، الانحرافات المعيارية)، بالإضافة إلي استخدام اختبار "ت" للعينة الواحد لاختبار فرضيات الدراسة، وقد كشفت نتائج الدراسة إلي: 1-مستوي توفير البيئة الإدارية والتنظيمية اللازمة في جامعة الزاوية لتطبيق الموازنة الصفرية للتقدم والنهوض بالجامعة للأفضل بدرجة مرتفعة. 2-مستوي توفر النظام المحاسبي الأساسي اللازم لتطبيق الموازنة الصفرية في جامعة الزاوية بدرجة منخفضة. 3-مستوي دعم وتأييد لإدارة جامعة الزاوية من قبل وزارة التعليم العالي في ليبيا لتطبيق الموازنة الصفرية للنهوض بالجامعة للأفضل بدرجة منخفضة. 4-مستوي تطبيق الموازنة الصفرية وفقا للخطط الموضوعة يؤدي إلي ترشيد النفقات في جامعة الزاوية بدرجة مرتفعة. الكلمات المفتاحية: المقومات الأساسية-الموازنة الصفرية-الجامعات الليبية. Abstract The availability of the basic elements for applying the zero-based budget to Libyan universities (Zawia University case study( e aim of the study was to identify the availability of the basic elements for the implementation of the zero budget in the Libyan University (a case study for Al-Zawiya University), the study community and its sample would be from Al-Zawiya University, and to achieve the goals of the study the descriptive analytical approach was used, and the study sample consisted of 45 financial department staff at, Al-Zawiya University, the study used a questionnaire, and the researcher used many descriptive statistical methods such as (arithmetic averages, standard deviations), in addition to using the "T" test for a single sample to test the study's hypotheses, and the results of the study revealed to: 1- The level of providing the necessary administrative and organizational environment at Zawiya University to apply the zero budget for progress and advancement of the university for the better with a high degree. 2- The level of availability of the basic accounting system necessary to implement the zero budget in Zawia University with a low degree. 3- The level of support and support for the management of Al-Zawiya University by the Ministry of Higher Education in Libya to implement the zero budget to advance the university to the best with a low degree. 4- The level of application of the zero budget in accordance with the plans laid down leads to a rationalization of expenditures at Zawia University with a high degree. Key words: basic ingredients - zero balance - Libyan universities.
Keywords: : المقومات الأساسية-الموازنة الصفرية-الجامعات الليبية.